PENGEMBANGAN KEPEMIMPINAN KEPALA SEKOLAH MTs NEGERI 15 JAKARTA (Education Journal : Journal Educational Research and Development, 2017)
This research is to find out the development of headmaster in Madrasah Tsanawiyah Negeri 15 Jakarta. The research method used is the case study method. Sampling technique using Moeleong's opinion is that in qualitative research no random sampling is examples of equipment. The completion technique is used Observation, interview and documentation. This research produces nine points, namely: 1) socialization program by the principal goes well. 2) The principal has a teaching schedule. 3) The organizational structure is clear. 4) School heads make short-term, long and long term Madrasah Principals programs. 5) Supervision of the principal that has been implemented. 6) Good communication system and excellent teacher board performance. 7) The role of principal as an innovator and motivator run. 8) What the Principal should do is to be active in his or her group organization. 9) Development of quality through the intensive and active assistance of the school package supervisor.